Non-invasive treatment of multiple enamel hypoplasia: A case report - Veličković, Milica (Medicinski časopis, 2022)
Developmental defects of enamel and dentin are caused by various etiological causes: hereditary and epigenetic factors, environmental factors and are created by their combined action. Developmental defects of enamel are described in the literature as defects resulting from negative effects on the dental lamina. Enamel hypoplasia is a quantitative disorder enamel deposition during the secretory phase and is characterized by a deficiency of the enamel, while hypomineralization is a qualitative disorder caused by incomplete mineralization and maturation of the enamel, accompanied by the porosity of the solid dental tissues and the opalescent tooth colour. The prevalence of hypoplasia is estimated at around 15.1%. Clinically, hypoplasia is a risk for caries, tooth sensitivity, erosion, and affects the aesthetic appearance of a patient with a psychological connotation. Early diagnosis, timely preventative methods and accompanying minimally invasive restorative treatment can correct anomalies and prevent possible complications.